The assessed value of the MBA programme by its alumni: The case of the former German military officers - Sebastiaan Derksen (Journal of Applied Leadership and Management, 2018)
Purpose: According to its proponents, an MBA programme can improve one's managerial and business competencies, knowledge and skills, and thus one's career chances in business. Worldwide many people make at least one or more career switches during their careers. Every year, among them are approximately one thousand German military of-ficers who make the career switch from the German army to business. In light of this context, this study focusses on the issue, whether the MBA programme does actually fulfil its proponents' 'promises of improvement' for its graduate students; former German military officers in particular. Methods: An empirical, quantitative research was conducted. 151 survey questionnaire responses were collected (55 former German military officers with an MBA degree and 93 civilian MBA alumni) to assess whether and to what extent the MBA programme is valued by its alumni for the improvement of their managerial performance and career success in business. Furthermore, this study tested the hypotheses that former German military officers value the MBA programme higher than civilian MBA alumni do, and that they value the MBA programme as an ideal study for a successful transition from a military career into business. Results: This study shows that both civilian MBA alumni and former German military officers with an MBA degree value the MBA programme positive in regard to the improvement of their managerial performance and career success in business. Although the results of this research do not show a real significant difference, former German military officers do value the MBA programme more positively than civilian MBA alumni do for the improvement of their overall success in business. It can be concluded that former German military officers assess the MBA programme as an ideal study to make the transition from army to business as successful as possible.
Keywords: 650; MBA; Management; Alumni; Alumni Management; career; Military Officer; Military Officers